Polarised strontium hydroxyapatite – xanthan gum composite exhibits osteogenicity in vitro. (2022) - Swain, Subhasmita; Kumari, Shubha; Swain, Priyabrata; Rautray, Tapash
Abstract: Clinical applications of bone tissue engineering demand that bone filler materials should be extremely biocompatible and osteoinductive so as to accelerate the repair of bone defects. Human bones under stress generate small electric charges thereby acting as a piezoelectric material. This has prompted researchers to investigate the properties of electrically active materials on bone tissue development. Herein, fabrication of bone filler material SrHA-Xanthan gum was done by a freeze-drying method. This study was directed to explore the effect of growth of surface charges on SrHA-Xanthan gum composite with respect to osteoblast activity in an artificial environment. Polarization of SrHA-Xanthan gum composites was carried out to induce negative charge on the composite surface and the specimen was then seeded with MG-63 cells. After 3 and 5 days of culture, cell viability on polarized composites were significantly increased as compared to non-polarized composites. On day 5 of culture, the relative expression of RUNX2, COL1, and OCN on polarized composites were elevated by 19%, 39%, and 35% respectively as compared to non-polarized composites. The present in vitro results suggest that negatively polarized composites can be favored over non-polarized composites (as implant materials) as they enhance osteogenesis and therefore present optimistic applications for bone tissue engineering.